ANALYSIS OF GUT FLORA FROM DAMP WOOD TERMITES (TRINERVITERMES SPP.) AND EXTRACTION, CHARACTERIZATION OF CELLULASE FROM THE ISOLATE - Narendrakumar G; Nmd, Saikrishna; P, Prakash; Tv, Preethi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study was to isolate, characterize, identify, and compare the potentials of cellulolytic strains isolated from the gut of damp wood termites (Trinervitermes species) collected from Chennai, Tamil Nadu, India. Methods: Termites were collected and used as hoard of cellulase producers and screened for the cellulase producers using carboxymethyl cellulose as the sole source of carbon and were authenticated using Congo red plate screening method. The isolates showing a significant zone of clearance were further confirmed by biochemically characterized. Results: Nine effective isolates were characterized and three strained were used for analysis. The organisms were subjected with substrate, temperature (25°C, 37°C, and 45°C), and pH to optimize the cultural condition. The enzyme activity was estimated using endoglucanase, FPase after incubating at appropriate conditions. Five isolates showing a significant zone of clearance were selected, out of which three belonged to Bacillus and one each to Staphylococcus. Optimization of media and genetic modification of the strains can further convalesce their competence. All the isolates have ensuring application in view of use in future. Conclusion: An effective strain of bacteria was isolated from the gut of termites can be used as a potential candidate for the production of cellulase in industries.